Exploring the potential of programmable button mouse in improving programmers efficiency - Azman F.; Aris H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Efficiency; Typewriter keyboards; Computer mouse; gaming mouse; Input devices; Keyboard shortcuts; Literature reviews; Optical mice; programmable button mouse; Specific tasks; Mammals